The impact of heavy Ga doping on superconductivity in germanium: Сверхпроводимость и сверхтекучесть - Skrotzki, R.; Herrmannsdörfer, T.; Heera, V.; Fiedler, J.; Mücklich, A.; Helm, M.; Wosnitza, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We report new experimental results on how superconductivity in gallium-doped germanium (Ge:Ga) is influenced by hole concentration and microstructure. Ion implantation and subsequent flash-lamp annealing at various temperatures have been utilized to prepare highly p-doped thin films consisting of nanocrystalline and epitaxially grown sublayers with Ga-peak concentrations of up to 8 at.%. Successive structural investigations were carried out by means of Rutherford-backscattering spectrometry in combination with ion channelling, secondaryion- mass spectrometry, and high-resolution cross-sectional transmission electron microscopy. Hole densities of 1.8·1020 to 5.3·1020 cm–3 (0.4 to 1.2 at.%) were estimated via Hall-effect measurements revealing that only a fraction of the incorporated gallium has been activated electrically to generate free charge carriers. The coincidence of a sufficiently high hole and Ga concentration is required for the formation of a superconducting condensate. Our data reflect a critical hole concentration of around 0.4 at.%. Higher concentrations lead to an increase of Tc from 0.24 to 0.43 K as characterized by electrical-transport measurements. A short mean-free path indicates superconductivity in the dirty limit. In addition, small critical-current densities of max. 20 kA/m2 point to a large impact of the microstructure.